PERSPEKTIF KEBIJAKAN BERBASIS BUKTI TERHADAP IMPLEMENTASI KEBIJAKAN MERDEKA BELAJAR KAMPUS MERDEKA - Denny Hernawan; Gotfridus Goris Seran; Irma Purnamasari; Agustina M. Purnomo; Afmi Apriliani (LPPM Universitas Djuanda Bogor, 2022)
For a university there is important to find out the effectiveness and to describe the implementation of freedom to learn independent campus (MBKM) policy in order to continually improve. Based on the perspective of evidence-based policy, the survey is conducted to obtain the evidences of two implementers of MBKM policy, namely provider (lecturer and administrative staff) and user (student). From provider’s perspective, results of the survey indicate the high level of provider’s involvement in implementing MBKM, starting from contribution to prepare MBKM through discussion/meeting/workshop to actively motivating students to participate in MBKM. The implementation of MBKM policy positively impacts on both student learning, improving student hard and soft skills, and improving lecturer capacity. From user’s perspective, results of the survey indicate student’s evaluation that the off-campus learning positively impacts on improving competence and widening perspective of student. The student also evaluates MBKM program in accordance with the need of graduate at future and the improvement of student soft skill. However, the survey identifies three main constraints in implementing MBKM policy, namely curriculum revision, redesign of academic information system, and fund problem for student.